To Compare the Effectiveness of Taping and Arch Support on the Flexible Flat Foot on a Random Population - J. Karthikeyan1, Kshtrashal Singh1, Susmitha Govind1, Kaviarasu Mahalingam1, Sree Vamsi1, Pavithra A (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Flat foot is also known as Pes planus caused by injury, prolonged stress on the foot, obesity,and faulty biomechanics. This will cause the posterior tibial tendon dysfunction, collapse of the foot archand developed flat foot (Pes planus).Objective: Many of the research studies show the prevalence of flexible flat foot is on raise in recent timesdue to any number of factors. The majority of researchers focused independently on the effectiveness ofKinesio taping and arch support. So we aim to compare the effectiveness of Kinesio taping and medial archsupport.Method: The study design is an experimental study. The study will be conducted at Aimst University, Kedah,Malaysia. Total of 30 participants of both the gender, age between 18 to 30 years, who have a limitation ofROM and pain while performing dorsiflexion and plantar flexion, will be recruited. Each participant willundergo pre-test and post-test screening for an assessment of Body Mass Index (BMI), ROM, pain, physicalexamination, and Staheli Arch Index. Later the participants will be divided into two groups by a convenientsampling method. Group A participants will undergo exercises related to strengthening of foot musclesalong with non-allergic taping technique while Group B participants will undergo exercises related to thestrengthening of foot muscles along with medial arch support.Data Analysis: Data collected is using IBM SPSS Statistics 23 for analyzing the data. For statistical analysisof the range of motion, VAS scale and Staheli Arch Index, Wilcoxon Signed Ranks Test was used. Tocompare the outcome of Kinesio Taping and Medial Arch Support, Mann-Whitney U test was used.Result: After statistical analysis, a significant improvement was found in the range of motion and VASScale. The level of improvement (p<0.05) was significantly high with Kinesio Taping in flat foot.Conclusion: The present study concluded that the application of Kinesio tape to flat feet was an effectiveintervention method for immediately reducing abnormally increased foot pressure and tone and stiffness inthe lower extremities muscles and considered to be the most effective intervention for subjects with flat foot.